Multi-scale grading utilization based on the characteristics of recycled concrete aggregates: a review - Feng, Qi; Liu, Binqing; Zhang, Yangpeng; Zhang, Chen; Wang, Dan (Frontiers in Materials, 2023)
The physical and mechanical properties of recycled aggregates (RA) among different particle sizes are compared. Results demonstrate that adhesive mortar content is a significant factor in determining the properties of recycled aggregate concrete (RAC). The adhesive mortar content on the surface of recycled aggregates is critical in selecting the most efficient strengthening treatment, and effects of the strengthening treatment on properties of RA with different particle sizes was reported. The utilization of RA was suggested to classify into fine powder aggregate, fine aggregate, coarse aggregate based on the particle size, i.e., the multi-scale grading utilization. The most suitable strengthening treatment was reviewed for RA with various particle size to improve the its utilization efficiency.